Hand-to-hand combat in the 21st century—INNOAGON warrior or modern gladiator?—a prospective study - Kruszewski, Artur; Cherkashin, Ilia; Kruszewski, Marek; Cherkashina, Elena; Zhang, Xiaoquan (Frontiers in Sports and Active Living, 2024)
Specific forms of physical activity are exercises related to hand -tohand combat in the broadest sense, often overlapping and containing similar elements associated with combat sports (for Western culture) and martial arts (for Far Eastern culture).There are many types of forms of practising hand -to-hand combat exercises, which can be seen as opposing or in some ways complementary, This study aims to investigate the development direction of the hand -to-hand exercises in Western culture, opposing the "traditional" and "modern" forms. Discussion: In this study, INNOAGON theory responds to the overuse of the term 'science of martial arts'. It is currently being used to promote extreme aggression and violence as an acceptable means of achieving success, and this model is expressively permeating other spheres of social interaction. In INNOAGON's understanding, hand-to-hand combat should be associated with the ancient thought of 'doing good' (ancient Greece) or 'wisdom' (Far Eastern cultures). The modern form of hand-to-hand combat, framed in these discussions as MMA or American pro wrestling, historically refers to the gladiatorial fights held during the Roman Games.Proper education, including education in the area of physical culture, leading to the development of a society turned towards values broader than just fun or self-satisfaction should be the basis for the development of the next generations. It actually remains to decide which path of social change we will choose: in the case of INNOAGON a positive one, and in the case of modern gladiator a destructive one.